(untitled) (Journal of the Bangladesh Agricultural University, 2017)
An experiment was conducted using a randomized complete block design to estimate genetic variability of ten rice genotypes. Analysis of variance for yield and yield contributing traits showed significant (p<0.01) variation among the genotypes. Results of genetic analyses showed a higher phenotypic coefficient of variation compared to their corresponding genotypic coefficient of variation for all the traits measured, which indicates that the traits were influenced by environment. The magnitude of difference between phenotypic coefficient of variance (PCV) and genotypic coefficient of variance (GCV) was less for the traits indicating little influence of environment. The higher estimates of PCV and GCV were observed for number of filled grains panicle1 (27.53; 26.84), number of unfilled grains panicle1 (26.76;25.28) and plant height (23.14; 23.00) indicates possibility of genetic improvement through direct selection for these traits, while days to 50% flowering, days to maturity, panicle length, number of effective tillers plant1, fertility (%), 1000 Seed weight and yield panicle1 showed low PCV and GCV values indicating the need for creation of variability by hybridization or mutation followed by selection. High heritability values (>60%) along with high genetic advance and genetic advance as percentage of mean were found for all the traits indicating prevalence of additive gene action, which provides good scope for further improvement by selection. J. Bangladesh Agril. Univ. 15(1): 15-19, January 2017